MENIMBANG AGAMA DALAM KATEGORI ANTROPOLOGI: Telaah terhadap Pemikiran Talal Asad - Novizal Wendry (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
This essay discusses Talal Asad’s critics upon definition of religion which has been formulated by Clifford Geertz. As an essentialist-anthropologist, Geertz defined religion as a system of symbols which acts to establish powerful, pervasive, and long-lasting moods and motivations in men. Based on Talal Asad’s reasoning, however, religion could not be defined simply as an analogy of words. When it is limited to a series of words there will be gaps of religious elements that are wrapped up, or the definition will load elements that arenot religion in-essence. For Talal Asad, words is imposibly far from socio-political factors. The former affects and changes the latter throughout the timeas does religion. It changes throughout the time in respond to and in line with social-historical contexts.Keywords: Talal Asad, Cliffort Geertz, Religion